An analysis of the functions of illocutionary acts used by the main characters in The Little Mermaid (2023) movie - Rahmanicka Bella Savitri; Anisa Nurjanah; Dorota Weclawski (Scientific English, 2026)
This study analyzes the functions of illocutionary acts used by the main characters, Ariel, Eric, and Ursula, in The Little Mermaid (2023) using Leech’s (1983) pragmatic theory. A qualitative descriptive method was applied, and the data were taken from the movie script, focusing on utterances that contain illocutionary meanings. The analysis identifies four functions of illocutionary functions: competitive, convivial, collaborative, and conflictive. Among these, the collaborative function is the most dominant. This indicates that most conversations in the movie are used to share information, explain intentions, give guidance, and build mutual understanding between characters. Competitive and conflictive functions appear in scenes that involve disagreement, pressure, or open conflict, especially in interactions related to power, authority, or manipulation. Meanwhile, convivial functions are found in polite and friendly expressions such as greetings, offers, congratulations, and expressions of gratitude. The dominance of the collaborative function shows that communication in The Little Mermaid (2023) mainly supports cooperation and helps move the storyline forward. In addition, this pattern highlights how language is used to clarify intentions, reduce misunderstanding, and support character development. Overall, this study demonstrates that illocutionary functions play an important role in shaping character relationships, conveying meaning, and supporting narrative development, while cooperative communication becomes a key pragmatic feature that strengthens the central themes presented.